2020
DOI: 10.1097/md.0000000000020365
|View full text |Cite
|
Sign up to set email alerts
|

Is postoperative hyponatremia a real threat for total hip and knee arthroplasty surgery?

Abstract: Postoperative hyponatremia (POH) is thought to be a fearsome complication of orthopedic surgery. Primary aim of this cohort study was to evaluate the incidence of POH and its clinical relevance in elective surgery, outlining differences between total knee arthroplasty (TKA) and total hip arthroplasty, looking for the presence of any risk factor commonly related to POH. Four hundred two patients that underwent total hip arthroplasty and total knee arthroplasty performed between 2016 and 2017 were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Four of those studies utilized large registry databases that, despite including larger cohorts, most likely had inherent biases because hyponatremia was identified using ICD codes as opposed to the actual laboratory measurements 18-20,25 . The remaining studies had smaller cohorts 4,5,7,9,10,16,17,24,26 , with the largest having a cohort of 2,009 patients, similar to our study 24 . Furthermore, several of those studies solely investigated the association between preoperative hyponatremia and perioperative outcomes 19,20,25 .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Four of those studies utilized large registry databases that, despite including larger cohorts, most likely had inherent biases because hyponatremia was identified using ICD codes as opposed to the actual laboratory measurements 18-20,25 . The remaining studies had smaller cohorts 4,5,7,9,10,16,17,24,26 , with the largest having a cohort of 2,009 patients, similar to our study 24 . Furthermore, several of those studies solely investigated the association between preoperative hyponatremia and perioperative outcomes 19,20,25 .…”
Section: Discussionsupporting
confidence: 77%
“…Although there has been a recent push to limit the routine use of laboratory tests in arthroplasty patients 13 , metabolic panels that include sodium levels are nonetheless commonly ordered at most institutions. Several factors have been found to be associated with the development of postoperative hyponatremia, including age, preoperative hyponatremia, the use of thiazide diuretics, and diabetes mellitus 4,9,10,14 . One recent study utilized machine learning algorithms to predict postoperative hyponatremia in a large cohort of TJA patients and noted that age, intraoperative blood loss, operative time, body mass index (BMI), and American Society of Anesthesiologists (ASA) classification were predictive 6 .…”
mentioning
confidence: 99%
“…6,9 In addition, evidence is accumulating that suggests routine post-operative electrolyte testing is not necessary for all patients. [1][2][3] Our finding that post-operative hyponatraemia is common but does not independently predict re-attendance at ED, and/or readmission to hospital within 90 days suggests that omitting routine post-operative electrolyte testing would leave common, mild, post-operative hyponatraemia unrecognised but that this may be safe. We acknowledge that patients captured here had their hyponatraemia recognised and, if appropriate, managed according to local guidelines, 11 and this may have affected outcome.…”
Section: Main Findingsmentioning
confidence: 89%
“…An accumulating body of evidence suggests that routine post-operative laboratory blood testing may not always be necessary and can perhaps be safely omitted in some settings. [1][2][3] Hyponatraemia, defined here as a s[Na] ≤ 135 mmol/L, is a common electrolyte disorder that, when encountered following surgery, often triggers a series of investigations and a prolonged hospital stay. 4,5 As enhanced recovery after surgery (ERAS) programmes become more popular, and the focus moves towards proactive and pragmatic perioperative care with shorter inpatient stays, there is a need to better identify those individuals who are likely to come to harm as a result of hyponatraemia, whilst minimising unnecessary tests for others who are likely to tolerate a small and short-lived drop in s[Na] without complication.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have attempted to determine which factors may be associated with the development of postoperative hyponatremia. These studies have identified several potential risk factors, including age, the need for blood transfusions, preoperative hyponatremia, electrolyte-free water balance, the use of thiazide diuretics, and diabetes mellitus 1,3,[5][6][7] . However, these studies were limited in that the study populations were small, and thus the studies were prone to being underpowered.…”
mentioning
confidence: 99%